English proficiency of information technology instructors and language use - Sarreal, Merigen L. (2008)
The study described the language use and English proficiency of information technology (IT) instructors based on the patterns and types of code switching they use, occurence and motivation for code switching, the relationship between the instructor's language proficiency and frequency of code switching, and the influence of length of service, gender, age, and educational qualification to the instructors' code switching. Thirty IT instructors from Metro Manila were observed for the transcription and tallying of their code swithcing. Data and survey forms and casual interviews were also used to gather information about the demographic profile of the respondents. Results showed that most code switching are single word switches and that IT instructors are frequent code switchers. Three types of lexical borrowing were also identified. Sentence switching has a significant relationship to instructors' language proficiency while the other aforementioned variables do not influence the frequency of code switching by IT instructors